Review of the leafhopper genus Protensus Zhang & Dai (Hemiptera, Cicadellidae, Deltocephalinae) with description of a new species - Zhang, Lan; Webb, M.d.; Xing, Jichun (Zootaxa, 2021)
Species of the leafhopper genus Protensus Zhang & Dai, 2001 (Deltocephalinae: Athysanini) from Japan and China are reviewed, and a new species Protensus lii sp. nov. is described and illustrated from China. Protensus nigrifrons Li & Xing, 2011 is treated as incertae sedis in the tribe Mukariini (Deltocephalinae). A checklist and key to species of Protensus is provided.